2021
DOI: 10.1016/j.chest.2020.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Sigh in Patients With Acute Hypoxemic Respiratory Failure and ARDS

Abstract: Background Sigh is a cyclic brief recruitment manoeuvre: previous physiological studies showed that its use could be an interesting addition to pressure support ventilation to improve lung elastance, decrease regional heterogeneity and increase release of surfactant. Research Question Is the clinical application of sigh during pressure support ventilation (PSV) feasible? Study Design and Methods We conducted a multi-center non-inferiority ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
0
23
0
2
Order By: Relevance
“…The proportions of sepsis-related ARDS combined with septic shock and MODS were >50 and >80%, respectively ( 8 , 19 , 20 ). In addition, most ARDS reports were focused on adults, especially elderly patients, who had more complications, such as chronic obstructive pulmonary disease, diabetes, chronic cardiac failure, and acute kidney injury ( 2 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of sepsis-related ARDS combined with septic shock and MODS were >50 and >80%, respectively ( 8 , 19 , 20 ). In addition, most ARDS reports were focused on adults, especially elderly patients, who had more complications, such as chronic obstructive pulmonary disease, diabetes, chronic cardiac failure, and acute kidney injury ( 2 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neste aspecto, em um ensaio clínico randomizado realizado por Mauri, et al 17 , que comparou o modo Ventilação por Pressão de Suporte (PSV) e PSV associado a suspiro, não foram encontradas diferenças expressivas em termos de relação PaO 2 /FiO 2 e desfechos clínicos importantes como: tempo de permanência hospitalar, dias de ventilação mecânica e mortalidade. Porém, foi demonstrado ser uma manobra segura, sem eventos adversos e sem danos teciduais.…”
Section: Discussionunclassified
“…Resultados semelhantes foram encontrados por Patroniti et al 11 ao demonstrar que, durante a administração da manobra de recrutamento com suspiros intermitentes, os parâmetros hemodinâmicos não sofreram quaisquer alterações significativas ao longo do estudo. Neste aspecto, Mauri et al 17 também não identificaram alterações hemodinâmicas, presença de barotraumas e arritmias significativas no grupo PSV com Suspiro versus grupo PSV, demonstrando ser uma manobra segura e possível de ser realizada sem prejuízos clínicos.…”
Section: Discussionunclassified
“…These criteria are similar to those discussed for controlled ventilation in ARDS [36] . Concerning the ventilator mode before weaning and extubation, a recent non-inferiority RCT comparing assisted ventilation and assisted ventilation plus sigh maneuver in acute hypoxemic patients concluded that in the sigh group, 23% of patients failed to remain on pressure-control ventilation, whereas 30% of patients in the assisted ventilation group (absolute difference, −7%; 95% CI, −18% to 4%; p = 0.015), demonstrating feasibility in using a sigh maneuver during assisted ventilation [76] .…”
Section: Rule 6 Assisted Ventilationmentioning
confidence: 99%
“…In phenotype 2, we suggest using moderate-to-high PEEP levels to improve lung recruitment; rescue therapies can be considered. In phenotype 3, we suggest using current recommendations for typical (non-COVID) ARDS [ [24] , 25 , [26] , [27] , [28] , 29 , [30] , [31] , [32] , [33] , [34] , [35] , 36 , [37] , [38] , [39] , 40 , [41] , [42] , [43] , [44] , [45] , 46 , [47] , [48] , [49] , [50] , [51] , 52 , [53] , [54] , [55] , 56 , [57] , 58 , [59] , [60] , [61] , [62] , [63] , [64] , 65 , [66] , [67] , [68] , 69 , [70] , [71] , [72] , [73] , [74] , [75] , 76 , [77] , [78] , [79] , [80] , [81] , [82] , 83 , 84 , [85] , [86] , 87 , [88] , [89] ,…”
Section: Coronavirus Disease 2019 (Covid-19) Ardsmentioning
confidence: 99%